the answer should be 8/7
when you are dividing expressions with exponents of the same letter,
you just subtract the exponents
so 3 - 3 = 0, therefore there would be no more t.
so 16/14 simplifies to 8/7
1)Simplify:(6x^3-16x^2+11x-5)/(3x-2) answer= 2x^2-4x+1-3over3x-2 2)Factor 27x^3-1 completley. answer= (3x-1)^3 if this isnt correct,im not sure how to solve it b/c this makes the most sense to me. 3)Simplify: x^2-3x-28 over x^2-9x+14,assume …
Can you please check my work? You have helped other students I know. Thank you:) Multiply -7(2a2 -4) = -14a2 + 28 Multiply 0.5(a + b -5) = 0.5a + 0.5b - 2.5 Factor bx - by + bz = b(x - y + z) Combine like terms (simplify) 12x + 4 -